UJI AKTIVITAS PENINGKAT DAYA INGAT FRAKSI ETIL ASETAT EKSTRAK ETANOL BUAH KEMUKUS (Piper cubeba L. f) PADA MENCIT JANTAN GALUR BALB/C DENGAN METODE RADIAL ARM MAZE (RAM) - Junvidya Heroweti; Yance Anas; Idress Muhammed Hama (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACTNeurodegenerative is often associated with aging. The aging process will affect the decrease in nerve cells, especially brain nerve cells. Ethyl acetate fraction of kemukus fruit ethanol extract (FEAEE) of kemukus fruit has been investigated as a memory enhancer with the Morris water maze (MWM) method. One of the shortcomings of the Morris water maze method is that it causes stress in test animals, thus affecting their memory. This study aims to determine the memory enhancing activity of FEAEE of kemukus fruit with the radial arm maze method This research is an experimental study with pre and posttest matched control group design using 25 male mice, Balb/c strains divided into 5 groups. Mice group 1 as a negative control group were given a 1% CMC Na solution of 17.5 mg/mL. Group mice 2 - 5 were given FEAEE of kemukus fruit with doses of 63, 126, 252, and 504 mg/kgBB, respectively. Test material is given orally for 21 days. Observations were made on the frequency of mice passing the platform correctly and incorrectly and calculating memory scores using the radial arm maze (RAM) method. Differences in memory scores were analyzed by the Mann Whitney test. The results showed that FEAEE steamed fruit has memory enhancing activity. Memory activity was indicated at doses of 63 and 252 mg / kg.Keywords: steamed fruit (Piper cubeba, L. f), ethyl acetate fraction, memory score, radial arm maze